Peran Kelompok Tani Terhadap Peningkatan Produksi Padi Sawah (Studi Kasus di Kelurahan Taroada Kecamatan Turikale Kabupaten Maros) - Wahyuni Z.; Abd. Asis Pata; Azisah Azisah (Universitas Muslim Maros, 2021)
This research was conducted in Taroada Village, Turikale District, Maros Regency. To select the sample using a simple random sampling with a precision of 10%. There are two data used, namely: primary data, namelydata obtained from observations through direct interviews and also through the help of a list of questionnairesand secondary data, namely data obtained from agencies/institutions related or related to this research. The purpose of this study was to determine the role of farmer groups in increasing rice production in Taroada village, Turikale district, maros regency. Data collected from the survey results using a questionnare and added with field observations. The data that has been collected is then tabulated to get real data that is used for analysis purposes. This study uses a likert scale analysis method to determine the role of farmer groups in incerasing rice production in Taroada village, Turikale district, maros regency. The results showed the role of farmer groups in increasing lowlang rice production, on average at the high category level with a percentage of 80,55% anf farmers rice production increased significantly due to implementing the row legowo planting system and being able to find out how to overcome pests and diseases such as neck rot